Gender Bias in Social Studies Education: Representation and Pedagogical Practices in Sociology Learning - Sukma Harya Nugraha (Gema Cendekia Institute, 2026)
This study aims to analyze gender bias in social studies education by focusing on two main dimensions: representation and pedagogical practices in sociology learning. It employs a critical literature review approach by examining academic sources and educational policy reports at both global and local levels. The analysis shows that gender bias is not only reflected in unequal representation within curricula and instructional media but is also manifested in pedagogical practices, including patterns of classroom interaction, teacher expectations, and assessment mechanisms. Such bias operates subtly through the hidden curriculum, which shapes students’ perceptions and learning experiences differently according to gender. In addition, local social and cultural contexts may either reinforce or mediate the reproduction of gender bias in education. These findings indicate that social studies education, particularly sociology learning, has not yet fully functioned as a space for critical reflection free from the very inequalities it seeks to examine. Therefore, a more reflective, inclusive, and critically oriented pedagogical approach is needed to promote equitable and emancipatory learning.